Towards EGTC: Evaluating Influence of the Perception of the Borders on the Cross-Border Policies and Cooperation in Serbia - Ocokoljic, Slobodan (Discussion Papers, 2013)
Serbia has had numerous transformations of borders during the last 20 years. There is no other country in the world that has witnessed this phenomenon in such a short period of time: from two types of federation to a unitary state; from self-governing socialism dominated by a single party to the authoritarian regime of Milosevic; and finally, the most recent transition to democracy. The phenomenon was followed by wars and strong media propaganda under which different territorial aspirations were presented to the majority of the population. Moreover, slow transition towards market economy and moderate progress in EU integration process influenced the high level of regional differences in Serbia. In the Republic of Serbia 46 Municipalities out of 150 are extremely underdeveloped, and their rate of development is under 60% of national average. This is in direct connection with insufficient capacities of the Republic of Serbia to meet the Copenhagen criteria regarding the capacity to cope with competitive pressure and market forces within the Union. The study’s relevance is rooted in the fact that only a small number of CBC projects and initiatives exist in Serbia. The local development sector has the second highest share of total disbursed IPA funds, around 10% from €11.5 billion for the period 2007–2013. This raises the question of CBC development impact within domestic absorption capacity, which is at 85.7%, slightly under the Western Balkans average of 87.3%. The problems of utilising funds available for CBC in the regions of the Republic of Serbia which are eligible for CBC under the IPA Programme are well known and already analysed in literature. Still, this instrument of European territorial cooperation, which also serves as a developing instrument of local self-governments, is not used to its maximum. This research aims at enhancing the understanding of perceptions of borders in the cross-border regions of Serbia, and to evaluate the influences of these perceptions using mental mapping and other classical applied social science methods on cross-border policies and cross-border cooperation as a potential development instrument for bordering Serbian municipalities. The present paper is based on two hypotheses. The first hypothesis is that borders are perceived as less important in regions with higher CBC. The second hypothesis is that more developed regions (higher GDP, more local institutions and actors, more CBC project) are already working, consciously or by chance, on the creation of CB territory which can be suitable for establishing of EGTC. In the end, the conclusion will try to argue what border regions are best prepared for the future establishment of EGTC once the legal bases are set and Serbia becomes a candidate country for the EU.